Neuronal involvement in muscular atrophy - Cisterna, Bruno A.; Cardozo, Christopher; Sáez, Juan C. (Frontiers in Cellular Neuroscience, 2014)
The innervation of skeletal myofibers exerts a crucial influence on the maintenance of muscle tone and normal operation. Consequently, denervated myofibers manifest atrophy, which is preceded by an increase in sarcolemma permeability. Recently, de novo expression of hemichannels formed by connexins and other none selective channels, including P2X7 receptors, TRPV2 channels were demonstrated in denervated fast skeletal muscles. The denervation-induced atrophy was drastically prevented in denervated muscles deficient in connexins 43 and 45. Nonetheless, the transduction mechanism by which the nerve represses the expression of the above mentioned none selective channels remains unknown. The paracrine action of extracellular signaling molecules including ATP, neurotrophic factors (i.e., BDNF), agrin/Lrp4/MuSK and acetylcholine are among the possible perpetrators of repression for connexin expression. This review discusses the possible role of relevant factors in maintaining the normal functioning of fast skeletal muscles and suppression of connexin hemichannel expression.